2021
DOI: 10.1111/apt.16589
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Physical and psychological comorbidities associated with irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) is one of the most common gastrointestinal disorders encountered by physicians in primary and secondary care. Patients with IBS commonly present with various extraintestinal complaints, which account for a substantial clinical and economic burden. The common extraintestinal comorbidities associated with IBS include anxiety, depression, somatisation, fibromyalgia, chronic fatigue syndrome, chronic pelvic pain, interstitial cystitis, sexual dysfunction and sleep disturbance. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 160 publications
3
40
0
Order By: Relevance
“…26 On the other hand, patients with chronic fatigue syndrome have a 35-92% prevalence of IBS. 18,27 Fibromyalgia was associated with a 1.54-fold increased risk of having IBS according to a national database, 19 whereas a review showed that 32% of women with fibromyalgia had IBS. 18 Up to 40% of patients with chronic pelvic pain fulfilled diagnostic criteria for IBS, and patients with migraine had IBS twice as often than those without migraine.…”
Section: Extraintestinal Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 On the other hand, patients with chronic fatigue syndrome have a 35-92% prevalence of IBS. 18,27 Fibromyalgia was associated with a 1.54-fold increased risk of having IBS according to a national database, 19 whereas a review showed that 32% of women with fibromyalgia had IBS. 18 Up to 40% of patients with chronic pelvic pain fulfilled diagnostic criteria for IBS, and patients with migraine had IBS twice as often than those without migraine.…”
Section: Extraintestinal Manifestationsmentioning
confidence: 99%
“…18 Up to 40% of patients with chronic pelvic pain fulfilled diagnostic criteria for IBS, and patients with migraine had IBS twice as often than those without migraine. [17][18][19] Patients with endometriosis have a two-to three-fold increased risk of IBS compared with controls and patients with interstitial cystitis have an 11-fold increased risk to have IBS compared with controls. 19 About half of the patients with sexual dysfunction also suffered from IBS.…”
Section: Extraintestinal Manifestationsmentioning
confidence: 99%
“…Awareness of comorbidities may help guide management decisions and may lead to a multidisciplinary approach to best address all physical and psychological comorbidities [26]. Establishing a diagnosis of IBS-D is important for patient reassurance and to minimize undue cost to the patient or health care system [26]. Given the symptom overlap between IBS-D and other disorders often encountered in primary care practices, consideration of other conditions can guide clinicians (Table 1) [20,[27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Comorbid Disorders: Testing To Exclude Ibsmentioning
confidence: 99%
“…Comorbid conditions are common in patients with IBS and can include anxiety and depression, chronic fatigue, fibromyalgia, and sleep disorders [ 25 , 26 ]. Awareness of comorbidities may help guide management decisions and may lead to a multidisciplinary approach to best address all physical and psychological comorbidities [ 26 ]. Establishing a diagnosis of IBS-D is important for patient reassurance and to minimize undue cost to the patient or health care system [ 26 ].…”
Section: Comorbid Disorders: Testing To Exclude Ibsmentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) is a disorder of gut-brain interaction (DGBI) that affects approximately 4% of the global population but estimates vary based on nonuniform study methodology [ 1 ]. Patients with IBS often display symptoms such as altered stool forms, constipation, bloating, and abdominal pain with overlapping co-morbidities including depression, anxiety, chronic fatigue, insomnia, sexual dysfunction, and fibromyalgia, collectively impairing quality of life [ 2 , 3 ]. A 2013 systematic review estimated the direct and indirect health care costs of IBS to be between $22–30 billion [ 4 ].…”
Section: Introductionmentioning
confidence: 99%